Anniversary of Russian association of endocrinologists - Natalya Pavlovna Makolina (Сахарный диабет)
24.02.2015 the Conference ?Endocrinology: from the very beginning to 21st century technologies? dedicated to 90th anniversary of Russian Association of Endocrinologists and foundation of State Institute for Experimental Endocrinology and 25th anniversary of Endocrinology Research Centre took place. The introduction speech was held by the president of Russian Association of Endocrinologists and chief of Endocrinology Research Centre, academician Ivan Dedov. The highly discussed topic was creation of National Endocrinology Centre with the main goal of implementation of modern technologies and association of endocrinology with closely related specializations such as immunology and neurology. Within the Conference their talks had the vice-president of Russian Association of Endocrinologists, academician Galina Melnichenko, scientific Secretary of Russian Association of Endocrinologists Marina Shestakova and the Board team member of Russian Association of Endocrinologists Valentina Peterkova.